2007
DOI: 10.5194/hess-11-584-2007
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication control in river-systems: an application of INCA-P to the River Lugg

Abstract: The Integrated Catchments model of Phosphorus dynamics (INCA-P) was applied to the River Lugg to determine the key factors controlling delivery of phosphorus to the main channel and to quantify the relative contribution of diffuse and point sources to the in-stream phosphorus (P) load under varying hydrological conditions. The model is able to simulate the seasonal variations and inter-annual variations in the in-stream total-phosphorus concentrations. However, difficulties in simulating diffuse inputs arise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…A full description of INCA-P, including process equations used, appeared in Wade et al (2002a) and an initial application is reported in Wade et al (2007). Only those parts relevant to this study are described herein.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…A full description of INCA-P, including process equations used, appeared in Wade et al (2002a) and an initial application is reported in Wade et al (2007). Only those parts relevant to this study are described herein.…”
Section: 2mentioning
confidence: 99%
“…A parameter set derived by the model developers, using expert calibration (i.e. manual changing of parameters) of INCA-P to the Lugg catchment, is used as a benchmark for comparing the results obtained from this GLUE analysis (Wade et al , 2007.…”
Section: 2mentioning
confidence: 99%
“…Many lakes have created serious eutrophication problems after the rapid economic development in foreign countries, so foreign countries started earlier in lake eutrophication control (Wade et al, 2007). As a result, these polluted lakes all recover well after a long period of using a "pollution first, treatment later" governance model.…”
Section: Strategies For Water Pollution Control Abroadmentioning
confidence: 99%
“…However, the information is very scarce for the P process. The observed P uptake rate for different crops and grassland for the catchments of UK and USA as reported in Wade et al (2007) has been used as a guide for determining P uptake rate. The details of the input parameters are also provided in Table 4.…”
Section: Model Setupmentioning
confidence: 99%